Spatial Permeability of Finnish Russian border - Luomi, Jesse (My University, 2025)
Current geopolitical climate in European Union land border is volatile amid Russian hybrid influence operations. There have, for example, been attempts at using migrants to destabilize border control measures of European Union member states. This has led to a closure of official border stations and temporal cease in handling of visa applications by Finnish authorities in Finnish Russian border. Regardless of the border closure, an elevated risk of illegal attempts to cross the border remains. While the authorities are monitoring the border area and preventing illegal crossings, it is important to have an understanding of spatial permeability along the border. Spatial permeability of Finnish Russian border was studied in 40-kilometer buffer area around the border line. Refined land cover data along with slope degrees and locations of border stations were used to produce friction layers that illustrate spatial permeability in the study area. Two scenarios were studied, the former considering effects of land cover and slope data, and the latter combining these with the locations of border stations. Friction layers were used for cost distance and cost pathway analyses, and optimal routes for border crossing were calculated from 10 towns in Russia to 13 destination towns in Finland. Results show that dense road networks in southern border areas effectively facilitate human mobility in otherwise challenging environments, while in the north the rural nature of the landscape combined with longer travel distances and lack of road networks acts as a barrier that decreases spatial permeability. Optimal paths across the border mostly used secondary roads to get close to the border and traverse short distances of less than a kilometer on either forests, grasslands or croplands to cross the border line. Spots of crossing the border line were mostly located in areas where secondary roads were closest to each other on both sides of the border, leaving the shortest possible distances to be covered on other less suitable land cover types.

Euroopan Unionin vihreän rajan tilanne on muuttunut epävakaammaksi geopoliittisten jännitteiden kiristyttyä Venäjän harjoittamien hybridivaikutusoperaatioiden vuoksi. EU:n maarajalla on nähty esimerkiksi yrityksiä horjuttaa jäsenvaltioiden rajavalvontaa, mikä on Suomen ja Venäjän rajalla johtanut rajan väliaikaiseen sulkuun sekä matkustusasiakirjojen tarkistuksen lopettamiseen. Riski laittomiin rajanylityksiin on silti pysynyt korkeana. Viranomaiset valvovat aktiivisesti rajaa ja pyrkivät estämään laittomat rajanylitykset, mutta kattava tilannekuva raja-alueen läpäistävyydestä on tärkeää. Tämä pro gradu -tutkielma käsittelee Suomen ja Venäjän maastorajan spatiaalista läpäisevyyttä 40- kilometrin puskurialueella rajan ympärillä. Tutkielmassa on käytetty jalostettua maanpeiteaineistoa, rinnekaltevuusmallia sekä raja-asemien sijainteja tuotettaessa kitka-aineistoja, jotka kuvastavat tutkimusalueen spatiaalista läpäisevyyttä. Analyysissä on käyty läpi kaksi skenaariota, joista ensimmäinen sisälsi maanpeite- ja rinnekaltevuusaineiston, ja jälkimmäinen yhdisti näihin raja-asemien vaikutuksen. Tuotettuja kitka-aineistoja käytettiin kustannus-etäisyys- sekä kustannusreittianalyyseihin, joiden perusteella määritettiin optimaaliset reitit 10 venäläisen ja 13 suomalaisen taajaman välillä. Tutkielman tulokset näyttivät, että tiheät tieverkot eteläisillä raja-alueilla edesauttavat ihmisten liikkumista muutoin haastavissa ympäristöissä. Pohjoisessa syrjäisyys, pitkät etäisyydet ja harvempi tieverkosto taas vaikeuttavat maantieteellisessä tilassa liikkumista ja vähentävät raja-alueiden läpäisevyyttä. Optimaaliset reitit kulkivat pääosin sivuteitä pitkin rajan läheisyyteen, jossa ne ylittivät rajan kulkemalla lyhyitä, alle kilometrin pituisia matkoja metsien, ruohikoiden tai viljelysmaiden läpi. Rajanylityskohdat olivat pääosin alueilla, joissa sivutiet rajan molemmilla puolilla olivat verrattain lähimpänä toisiaan, jolloin vähemmän läpäistävillä maanpeitteillä kuljettava matka oli mahdollisimman lyhyt.
Keywords: Spatial permeability, border security, migration, hybrid influencing